White Matter Abnormalities in 22q11.2 Deletion Syndrome: Preliminary Associations with the Nogo-66 Receptor Gene and Symptoms of Psychosis - Perlstein, Matthew D. (2013)
BACKGROUND: This study utilized diffusion tensor imaging (DTI) to analyze white matter tractography in anterior limb of the internal capsule (ALIC), fornix, and uncinate fasciculus (UF) of individuals with 22q11.2 Deletion Syndrome and controls. Aberrations in these tracts have been previously associated with schizophrenia. With up to 25% of individuals with 22q11.2DS developing schizophrenia in adulthood, we hypothesized reduction in structural integrity of these tracts, including an association with prodromal symptoms of psychosis. We further predicted association between allelic variation in a functional polymorphism of the NoGo-66 receptor gene and 22q11.2DS white matter integrity. METHODS: Tractography was conducted using fiber assignment by streamline tracking algorithm in DTI studio. Subjects were genotyped for the rs701428 SNP of the Nogo-66 receptor gene, and assessed for presence of prodromal symptoms. RESULTS: We found significant group differences between 22q11.2DS and controls in DTI metrics for all three tracts. DTI metrics of ALIC and UF were associated with prodromal symptoms in 22q11.2DS. Further, ALIC DTI metrics were associated with allelic variation of the rs701428 SNP of the NoGo-66 receptor gene in 22q11.2DS. CONCLUSIONS: Alterations in DTI metrics suggest white matter microstructural anomalies of the ALIC, fornix, and UF in 22q11.2DS. Structural differences in ALIC appear to be associated with the Nogo-66 receptor gene, which has been linked to myelin-mediated axonal growth inhibition. Moreover, the association between psychosis symptoms and ALIC and UF metrics suggests that the Nogo-66 receptor gene may represent a susceptibility gene for psychosis through its disruption of white matter microstructure and myelin-associated axonal growth.